Studi Deskriptif Karya Seni Rupa Berbahn Clay Tepung - Ilma, Dwika Tamara; Anggraini, Dwi; Hasnawati, Hasnawati (Universitas Bengkulu, 2024)
This study aims to describe the process of making art works made from clay flour and works of fine art made from clay flour in class IV A SDN 32 Bengkulu City. This type of research is qualitative, with participant observation techniques, and qualitative descriptive method. The research subjects were all students of class IV A 32 elemnetary school in Bengkulu City, totaling 20 students. The research instrument used was a human instrument (the researcher himself), by using observation guidelines and interview guidlines. Data collection techniques in the form of observation, interview, and documentation. Data analysis was carried out during the process of making the work and after the work was finished by referring to the fine arts elements and the principles of fine arts. Research results are (1)the process of making fine works of clay flour begins with preparing the tools and materials used, namely scissors, cutter, small rollers, straw, pins, toothpicks, cutton bud handles, ruler, lighters and painting brushes, followed by the implementation of making works from determining the theme, making shapes out of clay’s flour dough, laying out and arranging the forms that have been made and drying the work. (2) The results of artwork made with flour clay has used the guidelines elements of fine arts and the principles of fine arts, namely the elements of point, lines, fields, shapes, colors, textures and space. Then, the principle of unity, balance, rhythm, emphasis, proportion, and harmony.